EMISSIONS MONITORING OF HEAVY METALS AND THEIR COMPOUNDS RESULTED FROM COMBUSTION PROCESSES IN CLINKER KILNS IN ROMANIA - CRISTIAN CIOBANU; GHEORGHE VOICU; MAGDALENA – LAURA TOMA; PAULA TUDOR (Journal of Engineering Studies and Research)
With the dust arising from the clinker kilns and grill coolers (the major pollution sources in a cement plant), also heavy metals and their compounds (in the form of powders and vaporous), originating from fuels and raw materials, are pumped into the air. The paper presents some aspects regarding the monitoring of heavy metals contained in the combustion gases from a Romanian cement factory. The fuels used in the incinerator varied from coal/petroleum coke, refuse oils (from waste oils and their emulsions, up to sludge, paraffin, tars, contaminated soil), rubber (including whole used tires), plastic, paper, leather, textiles, wood (including sawdust), as such or impregnated/contaminated with various substances from industrial sources or sorted household wastes, sludge (previously dried) from wastewater treatment plants. In addition, the list of over 100 types of waste that can be co-processed can be found in integrated authorizations of cement plants. However, the level of heavy metals in the combustion gases was in allowed limits.